First Report of Liver Abscess Caused by Salmonella enterica Serovar Dublin - Qu, Fen (American Society for Microbiology, 2013)
This is the first reported case of liver abscess attributable to Salmonella serovar Dublin infection and also the fourth case of Salmonella liver abscess complicated with hepatocellular carcinoma reported since 1990. Drainage combined with intravenous antibiotics resulted in improvement, but recovery regressed again. Subsequent hepatic left lobectomy led to full recovery.